The Red badge of courage - Huston, John, 1906-1987; Reinhardt, Gottfried; Band, Albert, 1924-; Murphy, Audie, 1924-1971; Mauldin, Bill, 1921-2003; Dierkes, John, 1905-1975; Devine, Andy, 1905-1977; Crane, Stephen, 1871-1900.; Metro-Goldwyn-Mayer.; Loew's Incorporated; Copyright Collection (Library of Congress); Turner Entertainment Co. Collection (Library of Congress) (United States : Metro-Goldwyn-Mayer, 1951)
As a detachment of Union soldiers prepares for their first Civil War battle, a young private worries about his ability to endure the horrors of the battlefield. By contrast, his fellow soldiers seem fearless. During the first action he flees in panic, only to recover and fight bravely.
Copyright: Loew's Inc.; 14Aug51; LP1139.
Minor change version: [Colorized version]. -- United States : Turner International, 1951.
Copyright for minor change version: Turner Entertainment Co. DCR 1989; PUB 17Nov91; REG 22Jan92; PA586-498.
Archival positive (copy 2) to be used only as a theatrical projection print.
NCN012764; The Red badge of courage.
From the novel by Stephen Crane.
Keywords: War -- Psychological aspects -- Drama; Desertion, Military -- Drama; Courage -- Drama; Fear -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama; War films and programs; Features